2016
DOI: 10.1074/jbc.m116.757393
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enteritidis Effector AvrA Stabilizes Intestinal Tight Junctions via the JNK Pathway

Abstract: Edited by Luke O'NeillSalmonella pathogenesis studies to date have focused on Salmonella typhimurium, and the pathogenesis of a second major serotype, Salmonella enteritidis, is poorly understood. Salmonella spp. possess effector proteins that display biochemical activities and modulate host functions. Here, we generated a deletion mutant of the effector AvrA, S.E-AvrA ؊ , and a plasmid-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 59 publications
0
41
2
Order By: Relevance
“…Also stabilises intestinal tight junctions (Jones et al, 2008;Lin et al, 2016;Wu, Jones, & Neish, 2012) SlrP STM0800 t2087 a (STY0833) a SPA1952 a E3 ubiquitin ligase which mediates ubiquitination of mammalian thioredoxin and interacts with the chaperone ERdj3, leading to cell death (Bernal-Bayard, Cardenal-Muñoz, & Ramos-Morales, 2010;Bernal-Bayard & Ramos-Morales, 2009;Tsolis et al, 1999) (Continues) Absent Absent E3 ubiquitin ligase that interacts with the serine/threonine protein kinase PKN1 and inhibits NF-κB signalling (Haraga & Miller, 2003 SteA STM1583 t1493 (STY1482) SPA1285 Binds to phosphatidylinositol 4-phosphate (PI(4)P), localizes to SCV membranes and to Sifs. Also stabilises intestinal tight junctions (Jones et al, 2008;Lin et al, 2016;Wu, Jones, & Neish, 2012) SlrP STM0800 t2087 a (STY0833) a SPA1952 a E3 ubiquitin ligase which mediates ubiquitination of mammalian thioredoxin and interacts with the chaperone ERdj3, leading to cell death (Bernal-Bayard, Cardenal-Muñoz, & Ramos-Morales, 2010;Bernal-Bayard & Ramos-Morales, 2009;Tsolis et al, 1999) (Continues) Absent Absent E3 ubiquitin ligase that interacts with the serine/threonine protein kinase PKN1 and inhibits NF-κB signalling (Haraga & Miller, 2003 SteA STM1583 t1493 (STY1482) SPA1285 Binds to phosphatidylinositol 4-phosphate (PI(4)P), localizes to SCV membranes and to Sifs.…”
Section: Stm4157mentioning
confidence: 99%
“…Also stabilises intestinal tight junctions (Jones et al, 2008;Lin et al, 2016;Wu, Jones, & Neish, 2012) SlrP STM0800 t2087 a (STY0833) a SPA1952 a E3 ubiquitin ligase which mediates ubiquitination of mammalian thioredoxin and interacts with the chaperone ERdj3, leading to cell death (Bernal-Bayard, Cardenal-Muñoz, & Ramos-Morales, 2010;Bernal-Bayard & Ramos-Morales, 2009;Tsolis et al, 1999) (Continues) Absent Absent E3 ubiquitin ligase that interacts with the serine/threonine protein kinase PKN1 and inhibits NF-κB signalling (Haraga & Miller, 2003 SteA STM1583 t1493 (STY1482) SPA1285 Binds to phosphatidylinositol 4-phosphate (PI(4)P), localizes to SCV membranes and to Sifs. Also stabilises intestinal tight junctions (Jones et al, 2008;Lin et al, 2016;Wu, Jones, & Neish, 2012) SlrP STM0800 t2087 a (STY0833) a SPA1952 a E3 ubiquitin ligase which mediates ubiquitination of mammalian thioredoxin and interacts with the chaperone ERdj3, leading to cell death (Bernal-Bayard, Cardenal-Muñoz, & Ramos-Morales, 2010;Bernal-Bayard & Ramos-Morales, 2009;Tsolis et al, 1999) (Continues) Absent Absent E3 ubiquitin ligase that interacts with the serine/threonine protein kinase PKN1 and inhibits NF-κB signalling (Haraga & Miller, 2003 SteA STM1583 t1493 (STY1482) SPA1285 Binds to phosphatidylinositol 4-phosphate (PI(4)P), localizes to SCV membranes and to Sifs.…”
Section: Stm4157mentioning
confidence: 99%
“…In the current study, we report that the S. Enteritidis effector protein AvrA decreased Beclin-1 protein expression, thus impairing the autophagic response, for the benefit of The AvrA from S. Typhimurium is known as an anti-inflammatory effector that possesses acetyltransferase activity toward specific host MAPKKs and inhibits the host JNK/c-Jun/AP-1 and NF-κB pathways, but the role of AvrA from S. Enteritidis is less explored (9,(24)(25)(26)(27)(28). Here, we demonstrated that S. Enteritidis AvrA inhibited the autophagic response.…”
Section: Discussionmentioning
confidence: 80%
“…Beclin-1 is regulated by the JNK signaling pathway (30). Previous studies have shown that Salmonella AvrA inhibits the activation of the JNK signaling pathways (9,28). Using Western blotting, we found that the protein levels of p-JNK and p-c-Jun were higher in the S.E-AvrA --infected cells than in the cells infected by the S.E-WT or S.E-AvrA + strains (Fig.…”
Section: Avra Reduces Beclin-1 At the Protein Levels And Interacts Wimentioning
confidence: 70%
See 2 more Smart Citations